2010
DOI: 10.5897/ajb09.1501
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a bacterial strain for aniline degradation

Abstract: Aniline, a serious environmental threat and health risk to living organisms is being released into the soil and water bodies owing to its expanded use in industry. The objective of the present study was to isolate a strain from rhizospheric soil samples of wheat (Triticum aestivum L.) taken from an agricultural site near the industrial area of Faisalabad, with the capability of degrading aniline with its maximum activity. The isolated strain was identified as Staphylococcus aureus ST1 a newly reported strain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Mixed hydrocarbons were not degraded better Lidderdale (1993) whereas, the Caetano et al (2018) has reported that the presence of benzene inhibited toluene, xylene degradation. Different aromatic compounds released into the environment via various human-activities metabolized by soil-bacteria and is the foundation for cleanup technologies for enviornment ; Watanabe et al (1996);Haryama et al (1999). Elaborative studies are needed to clarify the taxonomic position of the micro ora for their biodegradation potential for other PAH's (polycyclic aromatic hydrocarbons) Braddock et al (1997).…”
Section: Microbiological Characterization Of Hydrocarbon Degrading Microbesmentioning
confidence: 99%
“…Mixed hydrocarbons were not degraded better Lidderdale (1993) whereas, the Caetano et al (2018) has reported that the presence of benzene inhibited toluene, xylene degradation. Different aromatic compounds released into the environment via various human-activities metabolized by soil-bacteria and is the foundation for cleanup technologies for enviornment ; Watanabe et al (1996);Haryama et al (1999). Elaborative studies are needed to clarify the taxonomic position of the micro ora for their biodegradation potential for other PAH's (polycyclic aromatic hydrocarbons) Braddock et al (1997).…”
Section: Microbiological Characterization Of Hydrocarbon Degrading Microbesmentioning
confidence: 99%